Smart Notifications – An ML-based Framework to Boost User Engagement - Pinto, Victor M. Magalhães; Oliveira, Leonardo M. Murtha; De Sousa, Ysabelle Pinheiro; Danyi, Stefania L.; Lima, Dimas S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2023)
The use of daily push notifications is prevalent in many online and mobile applications to enhance and maintain user engagement. Push notifications are often used in customer relationship management (CRM) campaigns to promote engagement, and frequently a customer is subjected to several on a daily basis and many at the same time. This often results in multiple notifications being scheduled to a user simultaneously. Also, in online apps, push notifications can trigger new orders during various shifts throughout the day for each user. This paper presents a complete framework of push notification modeling that takes into account the human-in-the-loop aspect of the problem, mixing up modeling with business decisions. The model structure is based on a two-tower deep learning model to rank push notifications based on their relevance to users, utilizing push metadata and user features. It also analyzes the causal impact of sending push notifications during each shift of the day. We use it to successfully optimize more than 100 million daily push notifications on the food delivery app iFood, resulting in increased orders and reduced average push notifications per user.